Pengaruh Penggunaan Media Sosial Terhadap Perilaku Belajar Siswa Pada Mata Pelajaran Ekonomi di SMA Muhammadiyah 4 Kota Bengkulu - Herwan MDK; Titania Putri Herdia (Universitas Dehasen Bengkulu, 2022)
This study aims to: To determine the effect of student social media on social studies subjects in SMA Muhammadiyah 4 Bengkulu City, to determine student learning behavior in social studies subjects at Muhammadiyah 4 high school Bengkulu City, to determine the effect of media on student learning behavior in social studies subjects at SMA Muhammadiyah 4 Bengkulu City. This type of research is a quantitative research. The population in this study is students / I SMA Muhammadiyah 4 Bengkulu City Class 10 and 11 Regular Social Sciences who are still active. The sample used is Total Sampling. Data collection techniques using observations, questionnaires, and documentation. Data Analysis Techniques using Simple Linear Regression. The results of this study indicate that: The Effect of Student Social Media on Economics Subjects at SMA Muhammadiyah 4 Bengkulu City is included in the High Category. It can be seen where the most respondents answered the questionnaire (Questionnaire) in the High category compared to other categories, namely with 24 respondents who received a percentage value of 0.53%. Student Learning Behavior in Economics Subject at SMA Muhammadiyah 4 Bengkulu City is included in the High Category. It can be seen where the respondents who answered the most questionnaires (Questionnaires) in the High category compared to other categories, namely with a total of 29 Respondents who obtained a percentage value of 0.64%. There is an influence of social media on student learning behavior in economic subjects at SMA Muhammadiyah 4 Bengkulu City. This is obtained from F count> F table (43> 4.07) and the level of influence is 95%.